Aplicación de técnicas activas en la lecto- escritura para el proceso de la enseñanza de aprendizaje de los niños y niñas del tercero, cuarto, quinto y séptimo año de educación general básica de la Escuela José H Gonzales del Recinto Pasagua, cantón Caluma, provincia Bolívar durante el periodo 2011 – 2012 - Pérez Núñez, Patricia Del Rocío (2011)
The research work, the application of techniques ACTIVE IN LITERACY FOR THE PROCESS OF TEACHING-LEARNING CHILDREN'S THIRD, FOURTH, FIFTH, SIXTH AND SEVENTH YEAR BASIC EDUCATION SCHOOL GENERAL JOSEPH H. GONZALES CALUM CAMPUS CANTON PASAGUA Bolivar Province DURING THE PERIOD 2011 to 2012. Its purpose is reading and writing are important communication skills of the child / a as well as their cognitive and personality, but many students find it difficult to learn to read and write and consequently are prone to school failure and low achievement levels not to have a good reading and writing. The importance of our subject is to find solutions through active techniques of reading and writing in order to achieve development, cognitive status, skills and abilities that children possess. The main objective in this work is to implement each of the techniques we have investigated in order to help both boys and girls and teachers as they are the main factors that students get quality education and first with respect to the background as that identified the reality of this problem as are deficiencies in the processes related to the Reading and Writing: Difficulties in writing, reading, reading comprehension, spelling and handwriting, and the teachers lack of knowledge evidenced the importance of these aspects in the teaching-learning process. The problem identified is consistent with the environment in which it develops the process of teaching and learning in the classroom of children / as the third, fourth, fifth, seventh year of basic education in the School Joseph H. Gonzales Pasagua Campus. The answer to the problem arises from lack of interest or unavailability of time available to teachers for activities that develop active techniques of literacy in the area of Language Arts. According to the general and specific, the same that have a high degree of reliability to ensure their validity and measurement range of the hypothesis testing, which identifies the two variables operacionalizadas, and in turn used to obtain the necessary elements for developing the tools of data collection. In Chapter I, the theoretical framework described issues directly related to the purpose of research is the application of active techniques in reading and writing for the process of teaching and learning of children / as the third, fourth, fifth, sixth and seventh year of Basic General Education School Joseph H. Gonzales in the area of Language Arts. In Chapter II, applies the methods that are based on the organization and execution of research work, the methods were inductive, deductive, logical historical, literaryand descriptive criteria, and explanatory correlation presented, in an easy andobjective, the universe and sample selection for the third, fourth,fifth, sixth, seventh year of Basic General Education applied to research subjects who were teaching these children as parents and as mothers quantifier population. Chapter III develops the results after the survey, the same that were tabulated and thoroughly as they are set up in tables and graphs, then interpret quantitative and qualitative, which leads to the verification the hypothesis and draw conclusions and recommendations are considered necessary. In Chapter IV of this research work is made available to the proposal based on the results of surveys conducted to several teachers in the area of Language and Literature, parents, children and girls in which you can verify that do not give importance to the Reading and Writing in the teaching-learning process of their children. It states that research, in which literacy is in the process of teaching and learning of the third, fourth, fifth, sixth, and seventh years of basic general education, allows a detailed diagnosis of the reality that there problems in the development of skills and abilities in children / as.